Analisis VCI Korelasinya Terhadap Kekeringan Lahan menggunakan Data Penginderaan Jauh Multi Temporal di Kecamatan Kubu, Kabupaten Karangasem, Provinsi Bali - Mahapati, Bintang Bayu; Trigunasih, Ni Made; Narka, I Wayan (Nandur, 2023)
This research analyzes drought occurrence in Karangasem Regency, specifically in Kubu District, Bali Province. Kubu District experiences drought disasters almost every year due to low rainfall and high temperatures. Decreased water supply has a significant impact on agricultural production, particularly on corn crops. To understand drought and its impacts, the Vegetation Condition Index (VCI) analysis method is employed using Landsat 8 satellite imagery. The VCI analysis results reveal significant drought occurrences in 2015, contributing to a decline in agricultural production. Data validation methods are utilized to verify the relationship between VCI and agricultural production through statistical data and field surveys. The validation confirms the adverse effects of drought on agricultural production in Kubu District. This research provides a better understanding of drought in the region and emphasizes the importance of using satellite data and VCI for drought monitoring.